PENGARUH KEPERCAYAAN DAN PROMOSI TERHADAP MINAT BELI SHOPEEFOOD : (Studi Kasus Pada Mahasiswa Universitas Advent Indonesia) - Hannah Chrissanty; Remista Simbolon (Journal Scientific of Mandalika (JSM) e-ISSN 2745-5955 | p-ISSN 2809-0543, 2022)
The level of customer desire to use a food delivery service provider platform is the urgency of conducting research to knowing the effect of trust and promotion on buying interest in the ShopeeFood application. This research uses a case study on students from Adventist University of Indonesia, primary data collection through questionnaires, and the use of purposive sampling method in selecting respondents. The results obtained from 106 respondents indicate that customer buying interest in the ShopeeFood application is influenced by the trust and promotion variables in the form of vouchers available at Shopeefood. This is indicated by the sign value of 0.001 < 0.05 and Fvalue > the Ftable value is 37.256 > 3.08 which gives positive results from the data processing process.